Lifestyle and Peptic Ulcer Disease - YEGEN, BERRAK (BENTHAM SCIENCE PUBL LTD, 2018)
The risk of developing Peptic Ulcer Disease (PUD) was shown to be associated with genetic inheritance, lifestyle and social status of the patients. Unhealthy lifestyle habits and failure in coping with stress have been closely associated with the occurrence of PUD. In contrary, limiting the use of analgesic drugs and glucocorticoids, controlling environmental and socioeconomic factors that predispose to H. Pylori infection, having a balanced diet, exercising regularly, coping successfully with stress, avoiding smoking, limiting alcohol intake and getting sufficient night sleep are essential in prevention and healing of PUD.
Keywords: nutrition; H. pylori; stress; NSAIDs; physical activity; sleep; alcohol; smoking; HELICOBACTER-PYLORI INFECTION; PHYSICAL-ACTIVITY REDUCE; DUODENAL-ULCER; ALCOHOL-CONSUMPTION; LIPID-PEROXIDATION; CIGARETTE-SMOKING; GUT MICROBIOTA; GASTRIC-ULCER; RISK-FACTORS; MELATONIN